2022
DOI: 10.1186/s12889-022-13875-6
|View full text |Cite
|
Sign up to set email alerts
|

Contextual factors influencing the urban mobility infrastructure interventions and policies for older adults in low- and middle-income countries: a realist review

Abstract: Transportation is among the key aspects that influence active ageing. This realist review intends to understand the mechanisms of urban mobility infrastructure interventions and policies in low- and middle-income countries for older adults and to identify factors, which influenced the success or failure of interventions. We followed the steps suggested by Pawson and colleagues for a realist review. Electronic databases were searched from inception until August 2020. Studies were screened based on titles, abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…It should also be a commitment of companies, who should be incentivized to think of sustainability policies from an age-friendly perspective as an added value to corporation targets. Moreover, in a recent review, Patil et al [91] reviewed 36 papers regarding mobility and active aging in many low-and middle-income countries around the world. The authors highlighted: (a) The need for policy makers to evaluate interventions and policy measures.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be a commitment of companies, who should be incentivized to think of sustainability policies from an age-friendly perspective as an added value to corporation targets. Moreover, in a recent review, Patil et al [91] reviewed 36 papers regarding mobility and active aging in many low-and middle-income countries around the world. The authors highlighted: (a) The need for policy makers to evaluate interventions and policy measures.…”
Section: Discussionmentioning
confidence: 99%
“…The MSAs can operate at three levels: a) distal (strategic actions at the higher level), b) intermediary (contextualisation of strategic MSAs at the operational level), and c) proximal (implementation of MSAs to generate health service and delivery and utilisation). This initial program theory further helped to inform the eligibility criteria and develop the search strategy for a systematic search and explaining/interpreting the findings [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that government interventions, such as fiscal expenditure efficiency (Zou, 2022), policies supporting the service sector (Zhunussova & Dulambayeva, 2019), and subsidies for public transport (Rabie & Burger, 2019), can significantly impact public transportation usage. Improving service quality has been linked to a higher acceptance of public transport, thereby promoting a shift from private to public modes of transportation (Patil et al, 2022). Government intervention plays a crucial role in ensuring the provision of high-quality public transportation services.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, assistance from the central government is essential for supporting public transport services and ensuring equality in service provision (Li & Deng, 2016). Various government interventions, such as educational initiatives and infrastructure enhancements, have been identified as key factors influencing the acceptance and utilization of public transport (Patil et al, 2022). Soft measures like information interventions and service improvements have also been identified as effective strategies for influencing mode choice and travel perception in public transport (Fan & Chen, 2020).…”
Section: Introductionmentioning
confidence: 99%